Experimental Evidence on the Long-Term Impacts of a Youth Training Program - Pablo Ibarrarán; Jochen Kluve; Laura Ripani; David Rosas Shady (Institute for the Study of Labor (IZA), 2015)
This paper presents the results of a randomized controlled trial on the long-term impacts of a youth training program. The empirical analysis estimates labor market impacts six years after the training including long-term labor market trajectories of young people and, to the best of our knowledge, is the first experimental long-term evaluation of a youth training program outside the US. We are able to track a representative sample of more than 3,200 youths at the six-year follow-up. Our empirical findings document significant impacts on the formality of employment, particularly for men, and impacts for both men and women in Santo Domingo, the capital of the Dominican Republic. The long-term analysis shows that these impacts are sustained and growing over time. There are no impacts on average employment, which is consistent with the low unemployment in countries with high informality and no unemployment insurance. Looking at the local labor market context, the analysis suggests that skills training programs work particularly well in more dynamic local contexts, where there is actual demand for the skills provided.
Keywords: J24; J64; O15; O17; 330; long-term; impact evaluation; randomized controlled trial; Dominican Republic; youth training; labor market outcomes